2013
DOI: 10.1016/j.cbd.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the protein components of a putative Calanus finmarchicus (Crustacea, Copepoda) circadian signaling system using a de novo assembled transcriptome

Abstract: Diel vertical migration and seasonal diapause are critical life history events for the copepod Calanus finmarchicus. While much is known about these behaviors phenomenologically, little is known about their molecular underpinnings. Recent studies in insects suggest that some circadian genes/proteins also contribute to the establishment of seasonal diapause. Thus, it is possible that in Calanus these distinct timing regimes share some genetic components. To begin to address this possibility, we used the well-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…Many of the deduced amino acid sequences of protein domains were highly conserved among different species, especially dbt, sgg and vri. It has been reported that the dbt, sgg and vri genes of the copepod Calanus finmarchicus show extensive sequence conservation with the corresponding genes in D. melanogaster, especially in functional domains (Christie et al, 2013). Many studies also suggest a high degree of evolutionary conservation between D. melanogaster dbt and sgg genes and those of vertebrates (Ruel et al, 1993;Fan et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Many of the deduced amino acid sequences of protein domains were highly conserved among different species, especially dbt, sgg and vri. It has been reported that the dbt, sgg and vri genes of the copepod Calanus finmarchicus show extensive sequence conservation with the corresponding genes in D. melanogaster, especially in functional domains (Christie et al, 2013). Many studies also suggest a high degree of evolutionary conservation between D. melanogaster dbt and sgg genes and those of vertebrates (Ruel et al, 1993;Fan et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Searches of the transcriptome assembly produced by Trinity were conducted using the DeCypher Tera-BLASTP algorithm on the Mount Desert Island Biological Laboratory’s TimeLogic DeCypher server (MDIBL, Salisbury Cove, ME, USA; http://decypher.mdibl.org/decypher/algo-tera-blast/tera-tblastn_an.shtml) as described in several recent publications (Christie et al, 2013a, 2013b). For all searches, the DeCypher program database was set to the combined Trinity assembly and a known fruit fly Drosophila melanogaster protein was used as the query sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of protein conservation and structure were conducted using a workflow described in Christie et al (2013a, 2013b). To identify the proteins most similar to each of the C. finmarchicus amine biosynthetic enzymes identified in this study, the deduced Calanus sequence was used to query the annotated protein dataset present in FlyBase (version FB2013_01), as well as the non-redundant arthropod protein dataset (taxid:6656) curated in GenBank (excluding C. finmarchicus proteins, obvious partial proteins, synthetic constructs, and provisional/unannotated hypothetical protein sequences); for both searches the blastp algorithm was used (Altschul et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, more limited starting material can often be used for the development of the transcriptome, and once produced, the resource provides a stable platform for the identification of essentially any protein of interest (e.g. Christie et al, 2013bChristie et al, , 2014aLenz et al, 2014), including neuropeptide precursors (e.g. Christie 2008aChristie ,b, 2014aChristie et al, 2008Christie et al, , 2010aChristie et al, , 2011aChristie et al, ,b, 2013aGard et al, 2009;Ma et al, 2009Ma et al, , 2010Toullec et al, 2013;Yan et al, 2012).…”
Section: Transcriptome Shotgun Assemblies: a Growing Resource For Pepmentioning
confidence: 98%